Tasas de crecimiento y acumulación de grados días de desarrollo en frutos de genotipos de cacao nacional en el valle del rio Carrizal - Basurto Rosado, Grey Beatriz (2023)
Cocoa is one of the most important industrial crops globally. The objective of the work was to identify the growth rates and the accumulation of degree-days of development in fruits in genotypes of national cacao, in the valley of the Carrizal river. The research was carried out during the year 2022 in experimental lots of the ESPAM-MFL polytechnic campus, located in El Limón site belonging to the Bolívar Cantón, Manabí. For the test, national cocoa plants in production were used, where two-centimeter fruit set were selected from the 10 cocoa clones under study (T1: EET-103, T2: EET-48, T3: EET-62, T4: EET -19, T5: EET-95, T6: EET-96, T7: EET-575, T8: EET-576, T9: EET-116, T10: CCN-51). A completely randomized design (DCA) was used. The recorded variables were fruit length; fruit diameter; dry weight of the fruit; weekly and monthly growth rate of the fruit; fruit relative growth rate (TCRF); absolute fruit growth rate (TCAF) and thermal units or degree days. The results showed that the treatment EET-19, EET-62, EET-48 and CCN-51 reached the physiological maturity of the fruit in an average time of 173 days, while the clones, EET-19, EET-62, EET- 48 and CCN-51 are later under the conditions in Bolívar cantón.